Prevalence of and Risk Factors for Lead Poisoning in Young Children in Bangladesh (Journal of Health, Population and Nutrition, 2013)
Lead poisoning is a major public-health problem in Bangladesh. A cross-sectional study was conducted to determine the extent of and risk factors for elevated blood lead levels (BLLs) in children in Bangladesh during September 2007July 2009. The study included 919 children aged less than 16 years. The children were recruited from six urban locations in Dhaka and one rural area in Chirirbandar, Dinajpur. In total, 495 (54%) children had high BLLs (>10 ?g/dL), with higher BLLs observed among children aged 5-9 years compared to children of other ages (p